Pengaruh Bimbingan Konseling Rational Emotive Behavior Terhadap Motivasi Belajar Peserta Didik Di SMP Negeri 35 Sinjai - Suriyati, Suriyati; Wahyuni, Sry; Harmilawati, Harmilawati; Anis, Muh.; Suriati, Suriati; Mulkiyan, Mulkiyan; Riska, Riska (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
This study aims to determine: the effect of the application of REBT counseling guidance on the learning motivation of students of SMP Negeri 35 Sinjai. This study is a quantitative study using the ex post facto method. The population of this study was all students in class VII.2 of SMP Negeri 35 Sinjai as many as 23 people consisting of 10 males and 13 females. The data collection techniques were questionnaires and documentation. The data analysis technique was quantitative research using statistical methods. The results of the study on the questionnaire sheet showed that the application of REBT counseling guidance had an effect of 32.7% on students' learning motivation. The results showed that Thitung counseling REBT 3.193> Ttable student learning motivation 2.085 and the significance value or probability was 0.004 <0.05, this means that Ha is accepted and H0 is rejected. Based on the description above, it shows that the implementation of REBT counseling guidance has an effect on the learning motivation of students at SMP Negeri 35 Sinjai.